Strain variation in susceptibility to monoclonal antibody-induced transplantation tolerance. - Davies, J; Cobbold, S; Waldmann, H (1997)
BACKGROUND: We have reproducibly induced specific tolerance to multiple minor histocompatibility antigens with nondepleting anti-CD4 and -CD8 monoclonal antibodies. The tolerance induced is effective for the lifetime of the host. We have tested this therapy in a number of mouse strain combinations to further understand the mechanisms. METHODS: Various mouse strains were grafted with allogeneic tail skin with and without nondepleting CD4- and CD8-specific monoclonal antibody therapy. The grafts were monitored daily for signs of rejection. RESULTS: Whereas the CBA/Ca (H2k) strain can be made tolerant to skin grafts that are mismatched at multiple minor histocompatibility antigens indefinitely, using the same protocol, long-term survival of similarly mismatched grafts on the HW80 (B6 congenic for BALB H1) mouse strain is limited to around 8 weeks. Interestingly, the B10.BR strain, which is also of the H2k haplotype, is also not readily tolerized. In addition, an F1 between the CBA/Ca and the resistant B10.BR strains is B10.BR-like in its susceptibility to tolerance induction. Susceptibility to such antibody-dependent tolerance induction is not related to immunogenicity because grafts mismatched at only a single minor antigen also do not reproducibly survive beyond 8 weeks when grafted onto HW80 mice in the presence of the antibody therapy. CONCLUSIONS: The data strongly suggest that the B6/B10 genetic background confers a level of resistance to CD4- and CD8-specific monoclonal antibody-dependent tolerance induction.